The Influence of Viral Marketing, and Product Innovation on Repurchase Intentions through Mediation of Purchase Decision - Muhammad Rosyihuddin; Sudarmiatin Sudarmiatin; Agus Hermawan (Almana : Jurnal Manajemen dan Bisnis, 2022)
With the existence of digital technology, the phenomenon of viral products in Indonesia is increasingly widespread, not only manufactured products, traditional products, or home products can also become viral because of this technology. The Sidayu (Bonggolan) traditional MSME products are no exception, which some time ago went viral on social media and then spread to the people of Gresik Regency and its surroundings. This research is very interesting to study, to study online consumer behavior towards product repurchase intentions which are characterized by theoretical studies that Viral Marketing, and Product Innovation influence purchase decisions and repurchase intentions while purchasing decisions are intermediaries. This type of research is explanatory research with a quantitative approach. The number of samples was 200 participants spread across Gresik Regency who had repeatedly bought this traditional food product. This study uses SEM analysis with the help of SmartPls software. The findings show that viral marketing and product innovation directly influence purchasing decisions, but the findings directly show insignificant results on repurchase intention. Interestingly, the findings of this study indicate that there is a significant indirect effect of viral marketing and product innovation on repurchase intention through the mediation of purchase decisions.